Eksplorasi Penggunaan Bahasa Arab Klasik dalam Pembelajaran Bahasa Arab Modern: Tantangan dan Peluang - Rahmah, Puja (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2025)
Classical Arabic (Fusha) and Modern Arabic differ significantly in structure, vocabulary, and usage. This study explores the challenges and opportunities of incorporating Classical Arabic into Modern Arabic instruction, focusing on its impact on students' language skills and cultural understanding. Using a case study approach, the research includes qualitative interviews and classroom observations to assess how teaching Classical Arabic enhances students' comprehension of Modern Arabic while identifying challenges such as grammatical complexities and vocabulary that may not be relevant to daily communication. The findings suggest that while Classical Arabic improves students' linguistic and cultural understanding, key challenges include its grammatical complexity and a lack of student engagement. However, the study also highlights opportunities to enhance academic skills and foster a deeper appreciation for Arabic literature and culture. The study recommends an integrated curriculum with contextualized teaching strategies to improve student motivation and comprehension, bridging the gap between Classical and Modern Arabic for a more comprehensive learning experience.